Banking of stem cells from deciduous teeth: from culture to clinics - K, Reena; CR, Sumanth; NG, Rajkumar; TR, Saraswathi. (Asian Journal of Medical Research, 2012)
Until recently, stem cells harvested from umbilical cord blood were the only storage option to guard against future illness or disease. Unfortunately, this opportunity comes only once and many parents regret missing it. Stem cells from human exfoliated deciduous teeth [SHED] are able to differentiate into a variety of cell types to a greater extent than many of the other post natal mesenchymal stem cells. SHED can be collected every time a milk tooth falls out. Banking SHED cells costs less than one third of the cost of cord blood storage. In addition, the proven facts that SHED can be directed to become pluripotential cells and generate solid tissue types, which cord blood cannot; has made them a simple, reasonable and convenient replacement to the umbilical cord blood. This review attempts to discuss the protocol, therapeutic applications and the present scenario of tooth banking.